Innovative Pedagogy: Improving Early Childhood Numeracy Skills Using Manipulative Media - Nurul Aien Abd Aziz; Sri Wahyuni; Pinky Narisa (Universitas Lancang Kuning, 2025)
This study aims to improve early childhood numeracy skills through the use of manipulative media in Class A of Al Ikhlas Kindergarten in Pekanbaru during the second semester of the 2023/2024 academic year. The research subjects consisted of 12 children (8 boys and 4 girls). The study used Classroom Action Research (CAR) in three cycles, with data collection methods including direct observation, photo documentation, and field notes. The research tools used for observation included a checklist to track children's ability to recognize and sequence numbers, match numbers with objects, and write numbers. The findings show significant improvement in numeracy skills across all cycles. At the pre-cycle stage, only 16.7% of the children demonstrated basic numeracy skills. After Cycle I, 50.6% of children were able to recite numbers 1-10 correctly. In Cycle II, 75% of the children could sequence numbers up to 20 and match numbers with objects. By Cycle III, 91.6% of the children showed strong numeracy skills, including writing numbers and distinguishing similar shapes, such as 6 and 9. The findings suggest that manipulative media, such as number blocks and number cards, are highly effective in improving early childhood numeracy skills. These results highlight the importance of using hands-on, interactive learning tools in early childhood education to foster cognitive development and engagement in learning. The study provides valuable insights into how educators can enhance numeracy education by incorporating manipulative media into their teaching practices, making learning more engaging and accessible for young children.